Analisis Kesehatan dan Keselamatan Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Badan Layanan Umum Daerah Pengelolaan Air Limbah Domestik (Blud Pald) Kota Bekasi - Dessy Wulandari; Hasanuddin; Djuni Thamrin; Zeinyta Azra Haroen (Mulia Pratama, 2023)
Some of the problems that occurred in BLUPALD regarding the work environment that affect the health and safety of employees so that it has an impact on employee performance. The working environment such as the air is not fresh due to the proximity of the office with piles of garbage and management of feces so that many employees experience mild illness with symptoms of cough, runny nose, diarrhea and fever which causes these employees to be unable to work and can cause their employee performance to decline. Types of Quantitative Research. Multiple Linear Regression statistical analysis method. The results of this study indicate that the variables of Occupational Health and Safety and the work environment simultaneously have a positive & significant effect on employee performance, then in the partial test Health and Safety variable has a positive & significant effect and work environment variable has a positive & significant effect.